AB0045 Low Molecular Weight-Baff Receptor Antagonists Suppress IGG Production by B Cells Co-Cultured with Monocytes. (15th July 2016) - Yoshimoto, K.; Suzuki, K.; Ishioka, E.; Nishikawa, A.; Sugahara, K.; Takeuchi, T.
Abstract : Background: We have previously reported that soluble BAFF (sBAFF) robustly increases IL-6 production in vitro by peripheral monocytes of patients with primary Sjogren's syndrome (pSS) and that the expression level of a BAFF receptor (BR3) is abnormally enhanced in pSS monocytes. Additionally, the proportion of BR3-positive monocytes to total monocytes was positively and significantly correlated with the sBAFF-induced IL-6 production by peripheral monocytes and the serum IgG level of pSS patients. These data collectively suggest that the elevated expression of BR3 in monocytes is involved in the pathogenesis of pSS which is often accompanied with hypergammaglobulinemia (HgG). Our findings also suggest that BR3 is a therapeutic target to treat pSS. However, no therapeutics has been available except antibodies against BAFF signaling so far. In this study, we show some of our latest data on low molecular weight compounds that inhibit a BAFF signaling pathway. Objectives: The purpose of our study is to discover low molecular weight BAFF receptor antagonists as drug candidates for pSS. Methods: High-throughput screening (HTS) of a chemical library was carried out to search for compounds that block binding of sBAFF to BR3. In brief, human BR3-expressing CHO-K1 cells were cultured in the presence of FMAT Blue-labeled sBAFF and each compound in 384-well plates, and the binding of sBAFF to BR3 was monitored by an Applied Biosystems 8200 Cellular Detection System. Hit compounds were further screened to eliminate false positives as follows: First, IFN-γ-stimulated THP-1, a human acute monocytic leukemia cell line, was cultured in vitro with sBAFF and primary hits, and the cumulative production of IL-6 was measured by ELISA. Second, sBAFF-stimulated pSS monocytes were cultured in vitro with or without pSS B cells in the presence of hit compounds, and IL-6 production by monocytes and IgG production by B cells were measured by ELISA. Results: A total of 18, 562 compounds were examined for inhibitory activities of sBAFF binding to BR3. Finally, two hit compounds, both of which were pyrrolopyrimidine derivatives (BIK12 and BIK13), were discovered and further investigated for biological activities. IL-6 production by sBAFF-stimulated peripheral pSS monocytes was significantly suppressed by BIK12 and BIK13 in a dose dependent manner. Similarly, IgG production by B cells cultured with sBAFF-stimulated peripheral pSS monocytes was also significantly suppressed by these compounds. Because sBAFF itself had no effects on IgG production by B cells, these data suggest that inhibition of BAFF binding to BR3 on monocytes caused suppression of IgG production by B cells in the co-culture probably through suppression of IL-6 production by monocytes. Conclusions: We have successfully discovered low molecular weight BR3 antagonists, pyrrolopyrimidine derivatives, by HTS and found that these compounds suppressed IgG production by B cells in a co-culture with monocytes. These compounds may provide not only lead compounds in drug development for pSS which often accompany HgG, but also novel tools to explore pathological mechanisms of pSS. Acknowledgement: We thank Dr.Takahiro Ito, Dr.Tomohiro Sugano, Dr. Ayumu Okuda, Dr. Hajime Yamada, Dr. Hiroyuki Ishikawa, Dr. Takeshi Doi, Dr. Takatsugu Hirokawa for their supports to establish HTS system. Disclosure of Interest: K. Yoshimoto: None declared, K. Suzuki: None declared, E. Ishioka: None declared, A. Nishikawa: None declared, K. Sugahara Employee of: Mitsubishi Tanabe Pharma Corporation, T. Takeuchi Grant/research support from: Mitsubishi Tanabe Pharma Corporation